Bifocals: Visualizing Interactions between Business Model Design and Ecosystem Innovation (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
This article describes an ongoing research project, which is mainly addressed to managers of nursing homes. Recent events have obliged nursing homes to redefine the interactions among stakeholders in their business ecosystem. By combining the existing literature in business ecosystem design and business model design, we propose a method called Bifocals to align the two ecosystem and business perspectives. We claim that our method (1) allows representing in details the niche ecosystem where the firm is located, (2) it offers a more structured way to respond to an ever-evolving ecosystem and (3) it underlines a coherent way to build and test new business model features to restructure the firm, in response to its ecosystem. We illustrate how to use Bifocals by describing how we supported the creation of a new service that adapts to recent evolution in the business ecosystem of nursing homes. In the future, we intend to validate our method by working with a group of nursing homes and health department officers.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.